Statin treatment for primary prevention of vascular disease: whom to treat? Cost-effectiveness analysis. (30th March 2011) - Greving, JP; Visseren, FLJ; de Wit, GA; Algra, A
Abstract : Objective To assess the cost-effectiveness of low dose statins for primary prevention of vascular disease, incorporating current prices, non-adherence (reduced clinical efficacy while maintaining healthcare costs), and the results of the recently published JUPITER trial. Design Cost-effectiveness analysis using a Markov model. Sensitivity analyses and Monte Carlo simulation evaluated the robustness of the results. Setting Primary care in The Netherlands. Participants Hypothetical populations of men and women aged 45 to 75 years without a history of vascular disease at different levels of risk for vascular disease (myocardial infarction and stroke) over 10 years. Interventions Low dose statin treatment daily versus no treatment for 10 years. Main outcome measures Number of fatal and nonfatal vascular events prevented, quality-adjusted life-years (QALYs), costs, and incremental cost-effectiveness ratios over 10 years. Results Over a 10-year period, statin treatment cost €35 000 (£30 000, $49 000) per QALY gained for men aged 55 years with a 10-year vascular risk of 10%. The incremental cost-effectiveness ratio improved as risk for vascular disease increased. The cost per QALY ranged from approximately €5000 to €125 000 when the 10-year vascular risk for men aged 55 years was varied from 25% to 5%. The incremental cost-effectiveness ratio slightly decreased with age after the level of vascular risk was specified. Results were sensitive to the costs of statin treatment, statin effectiveness, non-adherence, disutility of taking medication daily, and the time horizon of the model. Conclusions In daily practice, statin treatment seemed not to be cost-effective for primary prevention in populations at low risk of vascular disease, despite low costs of generic drug pills. Adherence to statin treatment needs to be improved to enhance the cost-effectiveness of the use of statins for primary prevention.